1989
DOI: 10.1016/0014-5793(89)80273-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 and phorbol ester stimulate tyrosine phosphorylation of overlapping substrate proteins

Abstract: FDC-PI is a murine myeloid cell line that requires interleukin 3 (IL3) for survival and proliferation. While the biological effects of IL3 have been well described, the biochemical mechanisms of IL3 actions have only recently been examined. We have investigated whether IL3 or PMA stimulates phosphorylation of proteins on tyrosine as well as on serine/threonine residues as previously described [(1986) Blood 68, 906-913; (1987) Biochem. J. 244, 683-691]. Here we report that both IL3 and PMA stimulate the tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…IL 3-induced phosphorylation of a 140 kDa protein in a murine cell line was originally reported by Koyasu et al (1987) and has been confirmed by the findings of several groups (Morla et al, 1988;Isfort et al, 1988;Sorenson et al, 1989a,b;Schreurs et al, 1989;Ferris et al, 1989). Two recent reports indicate that the 140 kDa tyrosyl-phosphoprotein observed after IL 3 stimulation may be the IL 3 receptor (Sorenson et al, 1989b;Isfort et al, 1988 (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…IL 3-induced phosphorylation of a 140 kDa protein in a murine cell line was originally reported by Koyasu et al (1987) and has been confirmed by the findings of several groups (Morla et al, 1988;Isfort et al, 1988;Sorenson et al, 1989a,b;Schreurs et al, 1989;Ferris et al, 1989). Two recent reports indicate that the 140 kDa tyrosyl-phosphoprotein observed after IL 3 stimulation may be the IL 3 receptor (Sorenson et al, 1989b;Isfort et al, 1988 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Previouswork addressing signal transduction byhaematopoietic cytokines has focused primarily on colony-stimulating-factorinduced phosphorylation in mouse myeloid cell lines (Evans et al, 1987;Sorenson et al, 1989a;Ferris et al, 1988Ferris et al, , 1989. Though mouse cell lines have served as a useful tool in elucidating the biology of the haematopoietic cytokines, ultimately it is critical to develop human models with which to conduct such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Disparate findings have been reported regarding the signaling pathways involved in this atypical tyrosine phosphorylation. Several studies using phorbol esters (22,23,64) have indicated a possible role for PKC in tyrosine phosphorylation. In permeabilized neutrophils, GTP-yS-stimulated increase in P-Tyr-protein levels was not mimicked by exogenous diacylglycerols (51), but the role of Ca2+ was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…The fl and y chains belong to the cytokine receptor family which has no catalytic domain like kinases. IL-2 induced, however, tyrosine phosphorylation of the fl and 7 chains of IL-2R [2,3] and of cellular proteins [4][5][6][7][8], and the IL-2R complex contained tyrosine kinase activity [3,9,10].…”
Section: Introductionmentioning
confidence: 99%